2020
DOI: 10.1080/13854046.2020.1840632
|View full text |Cite
|
Sign up to set email alerts
|

Online pharmacy navigation skills are associated with prospective memory in HIV disease

Abstract: Objective: The increased use of online pharmacy services in the midst of the COVID-19 pandemic provides an important backdrop against which to examine the role of neurocognitive functions in health-related Internet navigation skills among persons with chronic medical conditions, such as HIV disease. Prospective memory (PM) is reliably impaired in HIV disease and is related to laboratory-based measures of medication management capacity in other populations. This study examined whether PM shows veridicality in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…This interpretation is consistent with previous neuropsychological studies that have found memory to be a key aspect of financial management capacity in clinical and nonclinical populations, including older adults (e.g., Niccolai et al, 2017; Sherod et al, 2009), which likely implies that successful navigation on banking websites involves financial skills in addition to INS. Future studies might examine the contribution of prospective memory (PM), or future remembrance of intended actions, in online financial management skills as previous studies have found PM to be significantly associated with measures of financial management capacity (Pirogovsky et al, 2012) and online health navigation skills (Matchanova et al, 2021) among older adults with chronic health conditions. Future studies also may wish to examine the potential benefits of encoding strategies such as elaboration (e.g., paraphrasing the banking task instructions) or visualization (e.g., imagining completing the banking tasks) in online banking performance.…”
Section: Discussionmentioning
confidence: 99%
“…This interpretation is consistent with previous neuropsychological studies that have found memory to be a key aspect of financial management capacity in clinical and nonclinical populations, including older adults (e.g., Niccolai et al, 2017; Sherod et al, 2009), which likely implies that successful navigation on banking websites involves financial skills in addition to INS. Future studies might examine the contribution of prospective memory (PM), or future remembrance of intended actions, in online financial management skills as previous studies have found PM to be significantly associated with measures of financial management capacity (Pirogovsky et al, 2012) and online health navigation skills (Matchanova et al, 2021) among older adults with chronic health conditions. Future studies also may wish to examine the potential benefits of encoding strategies such as elaboration (e.g., paraphrasing the banking task instructions) or visualization (e.g., imagining completing the banking tasks) in online banking performance.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent validity for the TOPS has been supported through significant associations between the TOPS score and failures on the Medication Management Test-Revised (Heaton et al, 2004), a well-validated performance-based measure of medication management capacity, in a sample of 98 people with HIV (Matchanova et al, 2021). TOPS scores also are associated with multiple neuropsychological measures, although the Cambridge Prospective Memory Test predicted TOPS performance independent of global cognition, suggesting that prospective memory may be especially relevant for accurate online pharmacy use (Matchanova et al, 2021;Woods et al, 2016).…”
Section: Computer-use Testsmentioning
confidence: 98%
“…The diagnosis of HAND followed the Frascati criteria [25] and was based on age-adjusted scores from either the Cogstate [26] or the Cognition Battery from the NIH Toolbox [27]. The different batteries resulted from an administrative shift during the parent project, described in Matchanova et al [28]. The neuropsychological test data were summarized with the Global Deficit Score (GDS) [29], which converts individual T-scores to deficit scores that range from 0 (T-scores >39) to 5 (T-scores <20).…”
Section: Subjects and Biological Samplesmentioning
confidence: 99%